Diretriz curricular orientadora da educação básica de geografia do Paraná (2003 a 2013) e a prática docente: proposições, limites e descontinuidades - Mello, Cleonice Alves de (2014)
This research presents an investigation concerning the curricular orientation discipline of Geography in the State of Paraná , on the State Curriculum Guideline sare being used (or not) by the teachers of the state system of education in the areas cope of the municipality of Francisco Beltran . Among the objectives is to understand the fact as the process of preparing this guiding document occurred, which is appointed by the State as a result of a collective production. And to evaluate the applicability or lack thereof, of this curriculum framework in the practice of teachers belonging to state institutions located in the municipality of Francisco Beltran. In the grounds theoretical, we seek to understand the theory of the extended state Gramsci, based on Coutinho (1996) and Neves (2005). Pointed out the importance of the study on the state as an organization of political nature and power relations for understanding their logic as maintainer of public education and as a state educator. Regarding issue of Curriculum, based our contributions of YOUNG (2000), Forquin (1993), APPLE (1982), Lopes (2003), SACRISTÁN (2000), among other Brazilian authors, seeking to understand the function, as well as possible ideologies present therein. Historicisms briefly the process of preparation of DCEs in the state of Paraná analyzing government actions aimed the deployment and implementation of this curriculum targeting with its possibilities and limitations. The data systematization exults presented in the work of documentary research and interviews. Among the documents are analyzed curriculum documents of the discipline of Geography, focused for public schools in the state of Paraná network, such as DCE, Pedagogical Proposals Curriculum, Faculty Work Plans, as well as textbooks Geography used in schools covered in the survey. Also researched the records of SEED forwarded to schools and teachers on referral made to the development of DCEs and propose to involve teachers in the process. We performed analysis Proposals Pedagogical and Curricular Geography textbooks used by schools and state schools in the municipality of Francisco Beltran. We add to these, other information obtained through interviews with teachers of the discipline and the municipality in question regarding the use of this curriculum guidance. Thus resulting in a triangulation data from different sources , with which we made a parallel between these proposed documents and implemented by educators in the discipline of Geography , thereby targeting determine whether implementation of the DCE of Geography effected whether or not the praxis of educators of the area covered by the survey.